Scavenger receptor A-mediated nanoparticles target M1 macrophages for acute liver injury - Rongping Zhang; Shiqing Luo; Ting Zhao; Mengying Wu; Lu Huang; Ling Zhang; Yuan Huang; Huile Gao; Xun Sun; Tao Gong; Zhirong Zhang (Elsevier, 2023)
Acute liver injury (ALI) has an elevated fatality rate due to untimely and ineffective treatment. Although, schisandrin B (SchB) has been extensively used to treat diverse liver diseases, its therapeutic efficacy on ALI was limited due to its high hydrophobicity. Palmitic acid-modified serum albumin (PSA) is not only an effective carrier for hydrophobic drugs, but also has a superb targeting effect via scavenger receptor-A (SR-A) on the M1 macrophages, which are potential therapeutic targets for ALI. Compared with the common macrophage-targeted delivery systems, PSA enables site-specific drug delivery to reduce off-target toxicity. Herein, we prepared SchB-PSA nanoparticles and further assessed their therapeutic effect on ALI. In vitro, compared with human serum albumin encapsulated SchB nanoparticles (SchB-HSA NPs), the SchB-PSA NPs exhibited more potent cytotoxicity on lipopolysaccharide (LPS) stimulated Raw264.7 (LAR) cells, and LAR cells took up PSA NPs 8.79 times more than HSA NPs. As expected, the PSA NPs also accumulated more in the liver. Moreover, SchB-PSA NPs dramatically reduced the activation of NF-κB signaling, and significantly relieved inflammatory response and hepatic necrosis. Notably, the high dose of SchB-PSA NPs improved the survival rate in 72 h of ALI mice to 75%. Hence, SchB-PSA NPs are promising to treat ALI.